The Antecedents and Consequences of Social Media Marketing Adoption: Empirical Evidence from SMEs in Vietnam’s Tourism Sector - Thai, Nguyen Trong Minh; Minh, Huynh Thi Le (International Review of Management and Marketing, 2025)
Although the tourism sector in Vietnam is renowned for its rapid expansion, it also faces intense rivalry. Social media marketing (SMM) is a useful tool for small and medium-sized enterprises (SMEs) in this sector to improve business efficiency and maintain profits and growth. Recent studies have demonstrated the role of SMM in the business performance of SMEs. However, studies on SMM in the tourism industry are still scarce, especially in Vietnam. Therefore, this study was conducted to identify the antecedents and consequences of SMM adoption in SMEs in Vietnam’s tourism sector. The study applies the TOE framework to build a theoretical model and uses structural equation modeling (SEM) to evaluate the research hypotheses. Based on data analysis gathered from 345 managers and owners, the research findings show that there are five aspects in the TOE framework that impact SMM adoption. Additionally, the business performance of SMEs in the Vietnamese tourist sector is also positively and significantly impacted by the adoption of SMM. Therefore, SMEs in this industry can improve their business performance by effectively adopting SMM through the elements in the TOE framework presented in this study.